Strategi Peningkatan Keterampilan Pembelajaran Kurikulum Merdeka bagi Guru-Guru di Sekolah Menengah Pertama: Strategies for Enhancing Teachers’ Skills in Implementing the Merdeka Curriculum at Junior High Schools - Yuyun Nuriah; Dalmeri Dalmeri; Supadi Supadi (ITScience (Information Technology and Science), 2025)
This study aims to provide solutions to the problems faced by the partner institution, namely the lack of understanding of the Merdeka Curriculum, particularly in designing and developing Merdeka Curriculum teaching modules at SMP Negeri 187 Semanan, Kalideres District, West Jakarta. A team from Universitas Indraprasta PGRI Jakarta conducted a workshop in the form of training and mentoring to enhance teachers’ understanding of the Merdeka Curriculum. The mentoring activities were intended to broaden teachers’ perspectives and to review the implementation of the Merdeka Curriculum at SMP Negeri 187 through workshop-based activities. These workshops supported teachers in planning Merdeka Curriculum–based learning so as to improve classroom implementation in accordance with the subjects they teach. The mentoring method involved in-depth material delivery on Merdeka Curriculum–based learning accompanied by direct guidance for teachers. This program, carried out by the Universitas Indraprasta PGRI team, aimed to enhance teachers’ knowledge and provide hands-on practice in applying the Merdeka Curriculum learning system. The mentoring was implemented through intensive training and practical application of Merdeka Curriculum–based learning in the school context. The results of the mentoring activities indicate that teachers have gained a solid understanding of the Merdeka Curriculum and are able to implement it, starting from lesson planning through the development of teaching modules in accordance with learning guidelines and assessment frameworks for early childhood, primary, and secondary education. Learning assessments are able to measure targeted aspects and are holistic in nature. The mentoring program concludes that the activities were effectively carried out through the presentation of Merdeka Curriculum concepts for junior high school teachers, including the design of learning activities referring to Learning Outcomes (Capaian Pembelajaran/CP); explanations on developing learning sequences and objectives at the junior high school level based on institutional characteristics, students’ needs and interests, surrounding environmental conditions, and their alignment with CP. Consequently, learning sequences and objectives may differ across educational units. The teachers showed strong enthusiasm in participating in the training and responded that such training is highly important and necessary for them.